Simulation of Free Convection from an Inclined Heated Thin Plate in a Square Enclosure - Zahra, Qahtan Abdul; Mehdy, Ahmed N.; Sahib, Nora M. (Al-Khwarizmi Engineering Journal, 2009)
Simulation of free convection heat transfer in a square enclosure induced by heated thin plate is represented numerically. All the enclosure walls have constant temperature lower than the plate’s temperature. The flow is assumed to be two-dimensional. The discretized equations were solved stream function, vorticity, and energy equations by finite difference method using explicit technique and Successive Over- Relaxation method. The study was performed for different values of Rayleigh number ranging from 103 to 105 for different angle position of heated thin plate(0°, 45°, 90°). Air was chosen as a working fluid (Pr = 0.71). Aspect ratio of center of plate to the parallel left wall A2 take a constant and is equal to 0.5. The effect of the angle position of the heated thin plate on heat transfer and flow were addressed. With the increase of Rayleigh number heat transfer rate increased in both vertical and horizontal position of the plate. For the vertical situation (γ=90°) of thin plate, heat transfer becomes more enhanced than for the horizontal situation (γ=0°) and the inclined situation (γ=45°) especially when the value of aspect ratio A1 is equal to 0.25.